Pendampingan Penyusunan Laporan Keuangan Entitas Berorientasi Nonlaba Berdasarkan Isak 35 pada Madrasah Tsanawiyah Riyadlatul 'Ulum Batanghari - Esty Apridasari; Era Yudistira; Nining Istianatun Thoyibah (Jurnal Kabar Masyarakat, 2026)
As nonprofit-oriented entities, Islamic schools are required to prepare transparent and accountable financial statements in accordance with the Interpretation of Financial Accounting Standards (ISAK) 35. In practice, however, many educational institutions have established transaction recording systems but have not yet been able to present financial statements that comply with applicable accounting standards. This community service activity aimed to assist Madrasah Tsanawiyah (MTs) Riyadlatul 'Ulum Batanghari in preparing financial statements based on ISAK 35. The activity employed a participatory assistance approach consisting of initial needs assessment, dissemination of ISAK 35 concepts, account classification, financial statement preparation assistance, and review of the completed financial statements. The results indicate that the madrasah had implemented a transaction recording system, however, its financial reporting was still limited to cash receipts and cash disbursement summaries and had not complied with ISAK 35. Through the assistance program, the available financial transaction data were successfully transformed into a statement of financial position, statement of comprehensive income, statement of changes in net assets, statement of cash flows, and notes to the financial statements in accordance with ISAK 35. The program contributed to improving the quality of financial reporting, transparency, and accountability in the madrasah's financial management.